Pharmacological inhibition of SMYD2 protects against cisplatin-induced acute kidney injury in mice - Cui, Binbin; Hou, Xiying; Liu, Mengjun; Li, Qing; Yu, Chao; Zhang, Shenglei; Wang, Yi; Wang, Jun; Zhuang, Shougang; Liu, Feng (Frontiers in Pharmacology, 2022)
The histone methyltransferase SET and MYND domain protein 2 (SMYD2) has been implicated in tumorigenesis through methylating histone H3 at lysine36 (H3K36) and some non-histone substrates. Currently, the role of SMYD2 in acute kidney injury (AKI) remains unknown. Here, we investigated the effects of AZ505, a highly selective inhibitor of SMYD2, on the development of AKI and the mechanisms involved in a murine model of cisplatin-induced AKI. SMYD2 and trimethylated histone H3K36 (H3K36Me3）were highly expressed in the kidney following cisplatin treatment; administration of AZ505 remarkedly inhibited their expression, along with improving renal function and ameliorating renal damage. AZ505 also attenuated kidney tubular cell injury and apoptosis as evidenced by diminished the expression of neutrophil gelatinase associated lipocalin (NGAL) and kidney injury molecule (KIM-1), reduced the number of TUNEL positive cells，decreased the expression of cleaved caspase-3 and the BAX/BCL-2 ratio in injured kidneys. Moreover, AZ505 inhibited cisplatin-induced phosphorylation of p53, a key driver of kidney cell apoptosis and reduced expression of p21, a cell cycle inhibitor. Meanwhile, AZ505 promoted expression of proliferating cell nuclear antigen and cyclin D1, two markers of cell proliferation. Furthermore, AZ505 was effective in suppressing the phosphorylation of STAT3 and NF-κB, two transcriptional factors associated with kidney inflammation, attenuating the expression of monocyte chemoattractant protein-1 and intercellular cell adhesion molecule-1 and reducing infiltration of F4/80+ macrophages to the injured kidney. Finally, in cultured HK-2 cells, silencing of SMYD2 by specific siRNA inhibited cisplatininduced apoptosis of kidney tubular epithelial cells. Collectively, these results suggests that SMYD2 is a key determinant of cisplatin nephrotoxicity and targeting SMYD2 protects against cisplatin-induced AKI by inhibiting apoptosis and inflammation and promoting cell proliferation.